Democracy, citizens and populism: A conflictive articulation - Vilas, Carlos (2018)
This article centers on demonstrating that a type of democracy in Latin America, due to particular sociopolitical contexts of the region, is constituted by populism. In that sense, the author debates with the concept of democracy arising from the Latin-American experience, to later bring light over the political construction of the concept of “citizens”, as well as the elements that compose it, to finally, argue about the academic and political miscomprehension that the populist phenomenon has had, as well as its supposed incompatibility with democracy.